Synchronous and asynchronous online learning of advanced statistics during Covid-19 pandemic - Jackson Pasini Mairing; Rhodinus Sidabutar; Elyasib Yunas Lada; Henry Aritonang (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2021)
Online learning could have negative impacts on learning processes and outcomes. The condition needed to be resolved through the implementation of appropriate online learning approaches. The research was aimed at describing the effectiveness of the implementation of asynchronous and synchronous online learning approaches in students’ learning outcomes and skills of using Microsoft Excel on the Advanced Statistics of Mathematics Education Department from one of the universities in Central Kalimantan. The learning approaches were integrated with mathematics problems, Minitab software and Microsoft Excel, and videos. The research design was experimental research using a one-group posttest-only design. The subjects were chosen by clustered random sampling. They were 18 students of the department in the 2020/2021 academic year. The instruments were a lesson plan, several videos, textbooks, e-books, questionnaires, mathematics problems, mid-test, and final-test. The students learned using textbooks, e-books, and videos and solved the problems independently. Then, they discussed the solutions online in groups through their WhatsApp group (asynchronously). The problem solutions were presented by the students using a class on WhatsApp or video conference platforms (synchronous). The authors collected data by administering the questionnaire and the tests and analyzed the data using a -test and a Wilcoxon test. The results showed that the implementation of the approaches was effective in enhancing the learning outcomes and skills of using Microsoft Excel. Furthermore, most students positively responded to learn independently and all the students positively responded to analyze data using the software.